2020
DOI: 10.1039/d0dt02408b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and the anticancer mechanism of configuration-controlled Fe(ii)–Ir(iii) heteronuclear metal complexes

Abstract: Series of configuration-controlled Fe(II)-Ir(III) heteronuclear metal complexes, including ferrocene and half-sandwich iridium(III) complex units, have been designed and prepared. These complexes show better anticancer activity than cisplatin under the same...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Complexes of ruthenium with a potent antimetastatic agent NAMI‐A ( IV ) [ 26 ] and rhodium Rh(I) with ferrocene β ‐diketone ( V ) induced necrosis‐mediated cancer cell death and tumour cells hypoxia by radiosensitization. [ 27 ] From a series of ferrocenylpyridines and their complexes with platinum group metals, a Rh(I) complex with 3‐ferrocenylpyridine ( VI ) [ 28 ] and Ir(III) complexes with ferrocene‐modified bipyridine ( VII ) [ 29 ] and phenylpyridine ( VIII ) [ 30 ] hold promise as potential anticancer agents for further study (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of ruthenium with a potent antimetastatic agent NAMI‐A ( IV ) [ 26 ] and rhodium Rh(I) with ferrocene β ‐diketone ( V ) induced necrosis‐mediated cancer cell death and tumour cells hypoxia by radiosensitization. [ 27 ] From a series of ferrocenylpyridines and their complexes with platinum group metals, a Rh(I) complex with 3‐ferrocenylpyridine ( VI ) [ 28 ] and Ir(III) complexes with ferrocene‐modified bipyridine ( VII ) [ 29 ] and phenylpyridine ( VIII ) [ 30 ] hold promise as potential anticancer agents for further study (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, these complexes also exhibit similar or better anticancer activity and selectivity than the reported traditional half-sandwiched structrue Ir III complex (usually depicted as [(η 5 -Cp*)­Ir­(L ∧ L)­Cl]­PF 6 , L ∧ L = N ∧ C, N ∧ O, N ∧ N, N ∧ S, etc., Table S3). ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Meanwhile, these complexes also exhibit similar or better anticancer activity and selectivity than the reported traditional half-sandwiched structrue Ir III complex (usually depicted as S3). 9,18,29,30 Additionally, the substituents on TSC pro-ligands exhibit significant effect on the antitumor activity of Ir1−Ir4. It has been reported that hydrolysis is an important step toward classical half-sandwiched structure Ir III complexes, and M− OH 2 (hydrolysate) is usually more active compared to the corresponding complex.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that knowledge of these data will compose a very important part of the organometallic chemistry of graphene which is well-known to be a highly competitive, rapidly developing, and promising area of research. The strong interest in obtaining these data can be clearly understood from the fact of numerous examples of using cyclopentadienyl complexes of the group 8 metals as catalysts (Fe, Ru , ) or valuable precursors for different organometallic compounds (Os). Motivated by these examples, it would be of high interest to elucidate potential catalytic activity and chemical reactivity in general of the group 8 OMG complexes on the graphene surface. It should be noticed that, in a more general way, in the course of an inter-ring haptotropic rearrangement, as was mentioned earlier, the metal encompasses unsaturation and thus becomes prone to reaction with various incoming species. , Furthermore, it is very important to mention that large PAHs such as graphene and nanotubes were shown to have intrinsic anticancer activity. Also, numerous arene complexes of Fe, , Ru, ,,, and Os have been proven to possess anticancer activity. Therefore, we strongly believe that coordinating Ru or Os to very large PAHs could synergistically increase the anticancer activity of the resulting complexes, thus reinforcing the interest for studies of the stability, bonding and dynamical properties of the complexes similar to those shown in Figure ( 1 and 2 ).…”
Section: Introductionmentioning
confidence: 98%
“…11−13,15−20 Furthermore, it is very important to mention that large PAHs such as graphene and nanotubes were shown to have intrinsic anticancer activity. 74−76 Also, numerous arene complexes of Fe, 77,78 Ru, 33,35,36,79−81 and Os 34 have been proven to possess anticancer activity. Therefore, we strongly believe that coordinating Ru or Os to very large PAHs could synergistically increase the anticancer activity of the resulting complexes, thus reinforcing the interest for studies of the stability, bonding and dynamical properties of the complexes similar to those shown in Figure 1 (1 and 2).…”
Section: ■ Introductionmentioning
confidence: 99%